Validity of Ricardo Palma in the Centenary of his death - Arroyo Laguna, Eduardo (2019)
This article sustains the importance of Palma today as well as that of González Prada, both representing two moments of the critical conscience of Peru; Mariátegui and Haya de la Torre vindicate them. Lima creates the stage in which Palma will develop, marking its influences. Palma is an outstanding Peruvian who universalizes what is local, developing not only in the field of traditions, narrative, poetry, journalism, and theatre but also in the political field, having been deported several times.